Studying the Properties of Modern Thermal Insulation Materials - Tilovqobilov Nodirbek Nuriddin o’g’li; Karimov Gofur (European Journal of Life Safety and Stability (2660-9630), 2023)
Particular attention deserves the heat-insulating material - foam glass, which is an artificial silicate material with evenly spaced pores (0.1 ... 5.0 mm), separated by thin partitions of vitreous substance, has the necessary properties and, due to the foregoing, can be accepted for research aimed at its improvement (modification). The research results can be applied in the production of foam glass, which is used for thermal insulation of buildings and structures, equipment, pipelines, etc.